Fundamentos do ateísmo e a descrença no divino: reflexos subjetivos em relação ao discurso religioso - Rodrigues, Erick Henrique da Costa (2021)
This dissertation had the objective of understanding the phenomenon of atheism as a structuring aspect of disbelief in the divine. To this end, an investigation was carried out along the lines of the literature review research based on the qualitative approach. It is evident that, in the areas that see the religious phenomenon as an object of study, the atheistic manifestation, even with records prior to the Christian era, remains in places obscured in the repertoires of concepts made available to societies by the academic theoretical-methodological bias. In this sense that health promotion intends, it is necessary to determine whether in the forms of presentation of religious narratives is present a dialectical relationship with the prescriptions of religious discourses offered coercively, as well as to tell about the bond of the atheist subject with concepts previously portrayed with the filter of incompatibility, such as spirituality and meaning of life. Thus, it is noted that atheism belongs to the instance of human spirituality, that is, the condition of freedom of the subject over choosing not to accept, partially or entirely, all conceptual load of religious discourse and its interpretations of reality that aim to fill the search for meanings. The atheist does not have an experiential perspective discourse not consistent with the needs of his intrinsic questions, is a non-carrier of the deified interpretations of natural phenomena. Therefore, atheism is reactively positioned in the direction of what underlies the beliefs, of the ontological arguments of the gods, creating, conceptually, the possibility of a subject being an atheist to Olorum but theistic within the "Religions of the Book," of segregating Catholics and Protestants, Calvinists and Arminians.